New records of odontocete and mysticete predation by orcas in the Humboldt current system, South Pacific Ocean - García-Cegarra, Ana M.; Oña, Javier; Arancibia, Camilo; Aguilar, Luis; Toro, Frederick (Frontiers in Marine Science, 2024)
Orcas (Orcinus orca) are the top marine predators of the ocean, targeting multiple taxa including teleost fishes, elasmobranchs, seabirds, sea turtles, pinnipeds, odontocetes and other large cetaceans. According to their foraging strategies, genetics, acoustics, and morphology, orcas differentiate into ecotypes. Despite their cosmopolitan distribution, orcas are poorly studied in areas such as the Humboldt Current System of the Southeast Pacific coast. Since 2018 in northern Chile, presumed Type A orcas have been observed foraging on South American sea lions (Otaria byronia),benefiting from the presence of fishing vessels facilitating their hunt. These orcas were observed also pursuing large mixed groups of dusky (Lagenorhynchus obscurus) and long-beaked common dolphins (Delphinus capensis); however, predation on dusky dolphins was not documented. Here, we provide 28 additional sightings of orcas in two upwelling hotspots along northern Chile (15 around the Chañaral, Choros, and Damas Islandsin the Humboldt Penguin National Reserve from 2010–2023 and 13 in the Mejillones Peninsula from 2022–2023) and the first records of orcas effective hunting on dusky dolphins in this area. We present three new observations of orca tooth rake marks on fin whales (Balaenoptera physalus) dorsal fins in northern Chile. Furthermore, we observed the same orcas on two occasions foraging on dusky dolphins and sharing dolphin meat among group members. Overall, these observations suggest that orcas in northern Chile forage on marine mammals, especially on dusky dolphins, and the number of such predation events seems to be increasing near the coast.